Maturity Indicators and Adolescent Idiopathic Scoliosis: Evaluation of the Sanders Maturity Scale. Issue 7 (1st April 2018) - Neal, Kevin M.; Shirley, Eric D.; Kiebzak, Gary M.
Abstract : Study Design: Retrospective review. Objective: To determine the correlation between the Sanders Maturity Scale (SMS) and Risser stages, between both systems and menarche, and whether Risser can be used to predict SMS. Summary of Background Data: Predicting curve progression is critical to understanding adolescent idiopathic scoliosis and making treatment recommendations. The SMS is a better predictor of the curve acceleration phase of growth than the Risser stage. However, Scoliosis Research Society bracing criteria utilize the Risser stage and menarche. Methods: Consecutive female patients, 8 to 16 years old, evaluated for idiopathic scoliosis or spinal asymmetry over a 31-month period were included. Main curve size, Risser stage, menarchal status, and SMS stage were recorded for each encounter, and analyzed using Spearman rank correlation and regression models. Results: Six hundred fifty-six encounters (452 patients) were included with SMS staging, including 402 encounters that included menarchal data. The correlation between the Risser stage and the SMS stage was 0.9031 ( P  < 0.0001). However, ranges for the SMS at each Risser stage were large. Correlation between Risser stage and menarche was 0.7327 ( P  < 0.0001), and between SMS and menarche was 0.8355 ( P  < 0.0001). Eighty-five percent of SMS 3 patients were Risser 0, with or without open triradiate cartilages. Eighty-one percent of Risser 1 patients were SMS 4 or greater. Conclusion: When assessing maturity in idiopathic scoliosis, SMS correlates strongly with Risser stages, and both SMS and Risser correlate with menarche. However, Risser stage is a poor predictor of the exact SMS stage for individual patients due to the large ranges. The majority of patients who are ≥Risser 1 have passed the curve acceleration phase of growth. Developing brace criteria based upon the SMS stage may allow more accurate predictions regarding which patients will benefit from bracing. Level of Evidence: 2